Efeitos de um treinamento de Pilates na propriocepção e equilíbrio postural de mulheres idosas - Mezzomo, Stela Paula (2015)
The Pilates method (MP) is a system of exercises created by Joseph Pilates (1880-1967) which focuses on the strengthening and stabilization of the body, especially the abdominal region. This technique presents exercises that can be performed by different kind of people, contemplating body and mind to prioritize sensory-perceptual elements. For executing the exercises is required a high level of concentration, body awareness and muscle strength. Furthermore, proprioception and postural balance are also important during the execution. Aging implies a series of physiological and functional changes, including modifications in physical-motor skills. Thus, the aim of this study was to assess the effects of MP on postural balance and proprioception of elderly women. Therefore, the research was divided into two different papers. The first article aimed to evaluate the effects of MP in proprioception of the upper and lower limbs. The article number two assessed the postural balance in three different conditions: opened eyes (OA), eyes closed (OF) and in an unstable surface (BOSU balance). Participants were 25 women with a mean age 62,36 ±4,40 years (62,76±4,07 kg; 1,55±0,04 m), which never practiced MP. The subjects were divided into two groups: Pilates group (GP; intervention participants) and control (GC; without intervention). The intervention consisted of 24 sessions, twice a week, only on soil type, and consisted of exercises of basic and intermediate levels. In article 1, the instruments used to measure the levels of proprioception were a cinesiômetro (MS) and an analog fixed goniometer (MI). In the article 2, the variables of postural balance were measured by a force platform in the three conditions listed above. Data were analyzed with descriptive statistics. The normality and homogeneity of the data was analyzed using Shapiro-Wilk and Levene test, respectively for both articles. Then, comparison tests, intra-group and between groups, were performed. In article 1, the normality of the data was observed for MS variable, in the experimental and control groups. The variable MI didn t show normal distribution in both groups. In the second paper, the normality was observed only in the ellipse (OF). For the normal data, were used the paired t-test for intragroups measures and independent T test to detect differences between groups (GP and GC). For non-normal data, were used the nonparametric Wilcoxon test and the Mann-Whitney test, in both studies. The SPSS for Windows, version 20.0, was used for the statistical treatment for the data, with 5% significance level. There were statistically significant differences in proprioception in MS and MI, pré and post-program (p=0,0001 e p=0,008). There was no difference in intragroup comparisons (p>0,05). In article 2, the results showed statistical differences only for intragroups comparisons in the GP. In OA condition was observed differences in COPVelap and COPVelml variables; OF showed differences just in COPVelap; and the BOSU results presented minor fluctuations in the COP COPml variables ellipse area, COPVelap and COPVelml. The results show that a 12-week exercise program of MP, for elderly women, has generated significant improvements in proprioception MS and MI, when compared to control group. Regarding the variables analyzed and postural balance conditions, it was perceived statistical differences, in the post-test, only in intervention group, and they were more frequent in the BOSU condition.